Repellent effect of Essential oil from Ocimum basilicum against Rhyzopertha dominica (Coleoptera: Bostrichidae) and Tribolium castaneum (Coleoptera: Tenebrionidae) - Kumar , Ranjeet (Journal of Postharvest Technology, 2016)
The laboratory experiment was conducted to find out the repellent effect of  Ocimum basilicum against Rhyzopertha dominica and Tribolium castaneum by  paper disk method. Among the tested concentrations maximum repellency 98.20  percent was observed in 3 percent concentration of Ocimum basilicum followed by  90.06 and 88.38 percent at 2 and 1 percent concentration respectively against  Rhyzopertha dominica. The maximum repellency percentage 99.56 recorded at 3  percent concentration of Ocimum basilicum followed by 98.69 and 95.96 percent  at 2 and 1 percent concentration respectively. The tested essential oil from Ocimum  basilicum showed strong repellent effect against both stored grain insects.
Keywords: Essential oils; Repellency; Rhyzoprtha dominica Tribolium castaneum